Pathogenicity, enzymatic assays, and differential metabolomics to assess the virulence of fungal pathogens responsible for complex circular leaf spot (CCLS) disease of rubber trees in Malaysia - Sharifah Aliya, Syed Sagaff; Nusaibah, Syd Ali; Mohmad Mahyudin, Murnita; Yusop, Mohd Rafii (Academic Press, 2025)
The rubber tree (Hevea brasiliensis Muell. Arg.) is susceptible to an array of foliar diseases. A severe epidemic characterised by circular leaf spot symptoms on rubber leaves has recently infested rubber plantations in various rubber-producing countries, resulting in secondary leaf fall and a considerable production drop. This new disease is known as complex circular leaf spot disease (CCLS). The purpose of this study was to identify the causative pathogen(s) of CCLS disease using an in vivo pathogenicity test. Other than that, assessment of metabolites and leaf-degrading enzymes excreted by the causal pathogen(s) were carried out. The pathogenicity test was conducted using three-month-old rubber seedlings of clone PB 350. Microbe metabolite extraction was carried out on the potential isolated fungal pathogens, and the samples were subjected to gas chromatography-mass spectrometry (GC-MS) analysis. Four enzyme assays were also conducted: polygalacturonase (E.C. 3.2.1.15), pectin lyase (E.C. 4.2.2.10), endoglucanase (E.C. 3.2.1.4), and β-glucosidase (E.C. 3.2.1.21). Results from the pathogenicity test demonstrated that both fungi were able to initiate CCLS infections. Leaf inoculated with a spore suspension of Colletotrichum siamense produced the biggest mean lesion length, and the lesion resembled the symptoms of the disease in rubber plantations. Based on observations through a scanning electron microscope, the spores of C. siamense dominate the surface of the leaf lesions. Results from GC-MS analysis showed that microbial volatile organic compounds emitted by C. siamense have higher concentrations than those emitted by Pestalotiopsis jesteri. A total of 24 metabolites were detected in C. siamense and six metabolites in P. jesteri. In addition, C. siamense were also recorded to produce higher concentration of leaf degrading enzymes compared to P. jesteri in the enzyme assays conducted.